OXYGEN ISOTOPE STUDIES OF CARBONACEOUS CHONDRITES - A SURVEY - Clayton R.N.; Mayeda T.K. (My University, 1999)
The carbonaceous chondrites display the widest range of oxygen isotopic composition of any meteorite group, as a consequence of the interaction of primordial isotopic reservoirs in the solar nebula. These isotopic variations can be used to identify the reservoirs and to determine conditions and loci of their interactions. We present a comprehensive set of whole-rock analyses of CV, CO, CK, CM, CR, CH, and CI chondrites, as well as selected components of some of these meteorites. A simple model is developed which describes the isotopic behavior during parent-body aqueous alteration processes. The process of thermal dehydration also produces a recognizable effect in the oxygen isotopic composition.